Karakteristik Sensoris dan Kimia Hard Candy Dengan Substitusi Daun Sirih (Piper Betle L) dan Daun Suji (Dracaena Angustifolia) Tinggi Antioksidan - Fadillah, Ade Firman; Khotimah, Khusnul (Sekolah Vokasi, Universitas Sebelas Maret, 2024)
Hard candy is a type of candy that has a hard texture made from sucrose and glucose. In general, candy is consumed only as a snack. The aim of research by adding betel leaves and suji leaves to products is to provide health benefits, namely antioxidants. This research contains the hard candy production process by substituting betel leaves and suji leaves with quality ingredients including powdered betel leaves, powdered suji leaves, fructose sugar, stevia sugar and salt. The stages of the production process include preparing tools and materials, weighing the ingredients, making a solution of betel leaves and suji leaves, mixing the ingredients, heating, printing, cooling and packaging. This research used a Randomized Group Design (RAK) with one factor. This factor is the concentration ratio of lalijiwa mango fruit with added stevia sugar which consists of 3 levels (1%:7%), (2%:6%), (3%:5%). It was found that F1 was the best formula according to 33 panelists. The panelists' liking level for the best product formula based on color was 3.97, aroma was 3.33, taste was 3.75, texture was 3.39 and overall was 3.69. The content contained in betel leaf hard candy and F1 suji leaves is a water content of 3.1%; ash content of 0.31%; reducing sugar of 83.55% and antioxidants of 18.06%.